OBSERVATIONS ON VERBAL CODIFICATION OF PRION DISEASES (based on Latin and English) - Синиця, Валентина (SWorldJournal, 2022)
Studies of animal and human diseases as a result of the study of prions, under which, by definition, meaning «protein infectious agent from altered host protein molecules» is accompanied by appropriate terminological vocabulary. The term prion (Latin prio